Isolation of dental pulp and periodontal cells from human teeth for single-cell RNA sequencing - Pierfrancesco Pagella (Elsevier, 2021)
Summary: Teeth and the surrounding periodontal tissues are affected by many pathologies that compromise their integrity and significantly affect life quality. The study of the main dental tissues, the dental pulp and periodontium, is made arduous by their close association with highly mineralized tissues (dentin, cementum, and alveolar bone). Here we describe a protocol to isolate all cells composing human dental pulp and periodontium for single-cell RNA sequencing analysis.For complete details on the use and execution of this protocol, please refer to Pagella et al. (2021).